It Is Time for Zero Tolerance for Sexual Harassment in Academic Medicine. (February 2018) - Bates, Carol K.; Jagsi, Reshma; Gordon, Lynn K.; Travis, Elizabeth; Chatterjee, Archana; Gillis, Marin; Means, Olivia; Chaudron, Linda; Ganetzky, Rebecca; Gulati, Martha; Fivush, Barbara; Sharma, Poonam; et al.
Abstract : While more women are in leadership positions in academic medicine now than ever before in U.S. history, evidence from recent surveys of women and graduating medical students demonstrates that sexual harassment continues in academic health centers. Academic medicine's ability to change its culture is hampered by victims' fear of reporting episodes of harassment, which is largely due to fear of retaliation. In this Perspective, the authors describe efforts in scientific societies to address the issue of sexual harassment and to begin to establish safe environments at national meetings. The authors contend that each institution must work to make it safe for individuals to come forward, to provide training for victims and for bystanders, and to abolish "locker room" talk that is demeaning to women.